Possibilities for user-centric and participatory design in modular health care facilities - Lahtinen, Marjaana; Sirola, Pia; Peltokorpi, Antti; Aalto, Leena; Kyrö, Riikka; Salonen, Heidi; Ruohomäki, Virpi; Reijula, Kari (Intelligent Buildings International, 2018)
Many of today’s health care facilities are outdated and no longer efficiently support processes. The various development trends in changing health care services seem to support more frequent use of modular facilities. Modular facilities and their development, however, face the challenge of combining a customized, user-centric design for special customer needs with the rapid delivery of prefabricated facilities. The aim of this case study was to discuss the possibilities for and development needs of user-centric and participatory design in modular health care facilities. The results showed that due to time pressure, end-user involvement in design was rather low and applied participatory tools were limited. The prefabricated solutions set restrictions for planning, and compromises concerning the usability of the work environment had to be made. However, the end-users found the premises quite satisfactory. The study highlights the need to develop agile participatory design methods that are suitable for tight-scheduled modular construction. Since user participation in the workspace design of modular facilities encounters several challenges, the producers should also utilize user-centric knowledge from other sources. Systematic post-occupational follow up and evaluation of user experience, as well as utilization of evidence-based knowledge are important for the continuous improvement of the quality of modular buildings.
Keywords: modularity; well-being; usability; participatory design; work environment; health care